GLUTAMIN MEMPERCEPAT WAKTU PEMULIHAN JUMLAH SEL LIMFOSIT LIEN SETELAH AKTIVITAS FISIK MAKSIMAL PADA MENCIT (GLUTAMINE SHORTENS RECOVERY TIME OF LIEN LYMPHOCYTES AFTER EXCESSIVE PHYSICAL ACTIVITY IN MICE) - Jawi, I Made; Budiasa, Ketut (Jurnal Veteriner; Vol 8 No 2 (2007))
The immunologic? system? of the body requires? suitable recovery time after? excessive physical? activity. The recovery? time of spleen lymphocytes after? excessive? physical activity? in one? investigation was? 3? days. The? aim? of this? research is to identify?the role of? glutamine? in shortening? the recovery time of? spleen? lymphocytes? after?excessive physical activity. The? study? was conducted? on? 70? adults? Balb/c mice which? were? divided? into? 7? groups, with? a randomized control? group post-test? only design. In this? study? an observation? was made on? spleen? lymphocytes? of control, after? excessive? physical activity(in the the? form of swimming? until? near? drowning) with glutamine,? without glutamine ?and? after? the? recovery time of 1 and 2 days? of? each of? the 10 mice. Spleen? lymphocytes? were? counted in spleen preparation by mikroskop. The data obtained were tested? by? one way Anova. The findings? showed? that the number of spleen? lymphocytes significantly decrease after? excessive? physical activity?? in the?glutamine? and? non glutamine groups ( p < 0,05). The number of spleen? lymphocytes? was? not different as compered to control group or returned? to normal after recovery? time? of 1? day? in? the? glutamine group (p > 0,05 ). ?In the nonglutamine group the number of spleen lymphocytes was different from control group until 2 days ( p<0,05 ). From this finding it can be concluded that glutamine? shortens the recovery time of spleen lymphocytes? after? excessive? physical activity in mice.
Keywords: xcessive exercise, glutamine, recovery, spleen lymphocytes